Before she knew him : a novel - Swanson, Peter, 1968- (William Morrow, an imprint of HarperCollins Publishers, 2019)
From the hugely talented author of The Kind Worth Killing--the hair-raising tale of a young suburban wife who believes a killer is living right next door. And fears only the next murder, maybe her own, will make everyone believe her.